2006
DOI: 10.3917/nrp.002.0091
|View full text |Cite
|
Sign up to set email alerts
|

Le pari du métier face à l'anomie

Abstract: Distribution électronique Cairn.info pour Érès. © Érès. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable et écrit de l'éd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…However, it is necessary not to dissociate them too quickly. It has been shown that the stability of work collectives constitutes a precious resource for juggling with heterogeneous temporalities (Datchary, 2008) and that the profession was a necessary bulwark for management standards of autonomy (Osty & Dahan-Seltzer, 2006). The articles which make up this issue combine individual and organizational scales of analysis, and highlight different metronomes (dedicated functions, sociotechnical systems, narration, coaching), which each at their own levels and in their own ways contribute to temporal regulation.…”
Section: The Articles In the Issuementioning
confidence: 99%
“…However, it is necessary not to dissociate them too quickly. It has been shown that the stability of work collectives constitutes a precious resource for juggling with heterogeneous temporalities (Datchary, 2008) and that the profession was a necessary bulwark for management standards of autonomy (Osty & Dahan-Seltzer, 2006). The articles which make up this issue combine individual and organizational scales of analysis, and highlight different metronomes (dedicated functions, sociotechnical systems, narration, coaching), which each at their own levels and in their own ways contribute to temporal regulation.…”
Section: The Articles In the Issuementioning
confidence: 99%
“…Conséquemment, la question de l'intégration sociale, à l'intérieur des organisations se pose de manière aiguë. Et ceci d'autant plus que les métiers et corporations, socialement intégrateurs, tendent à disparaître au profit de dispositifs organisationnels reconnaissant toujours un peu moins la nécessaire autonomie des experts, des gens de métiers actuels (Osty, 2003 ;Osty et Dahan Seltzer, 2006).…”
Section: Suicide Et Intégration Socialeunclassified
“…The two men began to talk about metapsychics and the need for a serious laboratory devoted to the development of this science. Geley, who had not forgotten his earlier dream of an international institute, encouraged and helped Santoliquido to realize the project (Osty, 1930).…”
Section: An International Institute Of Metapsychics: Origins Creatiomentioning
confidence: 99%